An investigation on the shuttle trade dynamics of a small-open-economy - Afsin Sahin; Yilmaz Akdi; Cemal Atakan (International Journal of Economic Sciences and Applied Research, 2008)
In this article we have tried to assess the possible relationships between shuttle trade and the expletory variables and the expletory variables, export (f.o.b.), import (c.i.f.) and CPI based real effective US dollar exchange rate. We employed monthly data of Turkey covering the years from 1996:01 to 2006:12 and forecasted the parameters by Ordinary Least Square (OLS) estimation method. In order to find out whether there is a linear relationship among these series; we have checked each series whether are integrated at the same order or not. According to the ADF unit root test results, we have found that all the variables are integrated of order one, I(1), but shuttle trade. Besides we detected a case of multicollinearity among some of the expletory variables. Therefore we used first order autoregression model of shuttle trade. We have derived that, previous month's shuttle trade have positive impacts on the current level shuttle trade. We also used the same specification to indicate that the shuttle trade value increases in the months of fall and decreases in months of summer.
Keywords: F41; E26; C22; 330; international macroeconomics; shuttle trade; ordinary least square; Parallelimport; Außenwirtschaft; Lebenshaltungsindex; Kleines-offenes-Land; Autokorrelation; Methode der kleinsten Quadrate; Türkei